Cell types of origin for prostate cancer. (December 2015) - Lee, Suk Hyung; Shen, Michael M
Abstract : Analyses of cell types of origin for prostate cancer should result in new insights into mechanisms of tumor initiation, and may lead to improved prognosis and selection of appropriate therapies. Here, we review studies using a range of methodologies to investigate the cell of origin for mouse and human prostate cancer. Notably, analyses using tissue recombination assays support basal epithelial cells as a cell of origin, whereas in vivo lineage-tracing studies in genetically-engineered mice implicate luminal cells. We describe how these results can be potentially reconciled by a conceptual distinction between cells of origin and cells of mutation, and outline how new experimental approaches can address the potential relationship between cell types of origin and disease outcome.